Poivre noir Sarawak - Chan, Margaret Kit Yok (Universiti Teknologi MARA, Sarawak, 2017)
Poivre noir Sarawak literally means Sarawak black pepper. Every LJ morning, the Cours Saleya market is filled with a veritable I kaleidoscope of sights and smells with fresh produce, cheeses, olives, herbs, flowers, perfumed herbal soups and charm. This was in Nice, France where I took the picture in January when I was attending the kickoff meeting on the ERAMUS project funded by the European Union. I was given a very convincing sales talk by the stall owner trying to persuade me to buy “Le meilleur du poivre noir dans le monde", "The best black pepper in the world”. I looked at the price - 6 € for 50 grams. The packet on display cost 10 €.